Formation of Wakamono Kotoba in Shangri-La Frontier Manga - Mufti, Muhamad Alqi Nur; Arianingsih, Anisa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Wakamono kotoba refers to a type of Japanese language often used by young people in casual conversations. This language is marked by creative word-making processes such as shortening words, borrowing from other languages, changing sounds, and altering meanings. Wakamono kotoba appears often in Japanese pop culture, including anime, social media, and manga. Manga, in particular, often shows regular speech among young characters, making it a useful source for studying Japanese slang. This study seeks to examine how wakamono kotoba is formed in the manga Shangri-La Frontier. The research uses a qualitative descriptive method. The data includes wakamono kotoba expressions found in the dialogue of Shangri-La Frontier Volume 1. Data were gathered through observation and note-taking. The analysis follows Yonekawa’s classification of wakamono kotoba formation, which covers processes like shortening, borrowing, combining, and other creative ways of forming words. The results indicate that in the manga, wakamono kotoba expressions are frequently created by shortening loanwords and combining them. These formations show the linguistic creativity of Japanese youth and the ongoing evolution of informal Japanese language in today’s popular culture.